2015
DOI: 10.1186/s12957-015-0448-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and oncological outcomes in Chinese patients with renal cell carcinoma and venous tumor thrombus extension: single-center experience

Abstract: BackgroundTo evaluate the clinical and oncological outcomes and to identify prognostic factors for survival in Chinese patients with renal cell carcinoma (RCC) and venous tumor thrombus (VTT).MethodsA total of 86 patients who underwent nephrectomy and tumor thrombectomy for RCC and venous tumor thrombus extension from 2003 to 2013 were included in this retrospective study. The records of these patients were reviewed. Kaplan-Meier analysis was used to determine cancer-specific survival (CSS). Prognostic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 30 publications
4
35
1
1
Order By: Relevance
“…IVC wall invasion has recently been recognized as an independent prognostic factor for the survival of patients with IVC thrombi [ 16 , 18 20 ]. During surgery, IVC wall invasion requires a very challenging reconstruction beyond standard cavorrhaphy, that might include segmental resection or prosthetic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…IVC wall invasion has recently been recognized as an independent prognostic factor for the survival of patients with IVC thrombi [ 16 , 18 20 ]. During surgery, IVC wall invasion requires a very challenging reconstruction beyond standard cavorrhaphy, that might include segmental resection or prosthetic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Since single variable hardly accurately predict the prognosis of patients with RCC and VTT, several studies analyzed the predictive value of clinicopathological parameters in these patients. The significant predictors of long‐term survival include tumor thrombus level, tumor size, Fuhrman grade, lymph node invasion, metastasis at surgery, and adrenal gland invasion . However, no prognostic model has been established in these study which hinder the clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…include tumor thrombus level, tumor size, Fuhrman grade, lymph node invasion, metastasis at surgery, and adrenal gland invasion. [8][9][10] However, no prognostic model has been established in these study which hinder the clinical application. Haddad et al 11 reported a preoperative nomogram for risk assessment in patients with RCC accompanying a suprahepatic IVC thrombus.…”
mentioning
confidence: 99%
“…The authors did not perform a subgroup analysis of patients affected by both RCC and VTT versus patients without VTT. Chen et al also investigated the impact of renal pelvis invasion on survival in patients with RCC and VTT [ 20 ]. Fifty-three patients had level 0 VTT, 16 level I, 11 level II, and 6 level III.…”
Section: Discussionmentioning
confidence: 99%